Topology optimization design of wing rib based on bi-directional evolutionary structural optimization method - HUANG Chenglei; FAN Qingming; LIU Hongjun; YU Boya (Xibei Gongye Daxue Xuebao)
As an important part of the solar UAV, the weight of the wing occupies the majority of the proportion of the overall structure. However, the solar UAV has very strict requirements on the weight of its own structure. The topological optimization of the wing fin structure can be usually carried out to meet the structural strength and reduce the quality of the wing structure as much as possible, which is of great significance for improving the overall performance of the UAV. Taking the wing of a solar UAV with high aspect ratio as the research object, based on the objective function of the minimum strain energy of the whole wing and the volume fraction of the wing fin, the topology optimization design of the wing fin was carried out by using the bidirectional progressive structure optimization method. The internal materials of the wing fin were added or deleted reasonably according to the element stress, and the optimized wing fin was redesigned. Finally, the overall weight of the wing was reduced by 29.7%. The results show that this method can obtain the optimal configuration of the wing fin, effectively improve the utilization rate of materials, and greatly reduce the weight of the wing structure, which provides a certain reference for the lightweight research of solar UAV.